DISEMINASI TEKNOLOGI PEMBUATAN PAKAN BUATAN ALTERNATIF DENGAN CAMPURAN LIMBAH KANGKUNG AIR, Ipomoea aquatica Forks, UNTUK PEMBUDIDAYA IKAN DI SUMATERA BARAT - Efrizal Efrizal; Rusnam Rusnam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2017)
Community service activities is carried out with the purpose of waste utilization water spinach, Ipomoea aquatica Forks, as a raw material alternative to artificial feed and improve the knowledge and skills of the fish farmers (the community) Village Koto Tangah in the business of making the feed / pellets fish in West Sumatra. The method used in this activity are (1) Lectures, and (2) Demonstration of making flour from waste water spinach and manufacture pellets / alternative fish feed with water spinach flour mixture. From the results of this IbM service activities found that the knowledge and skills of Sawah Laweh farmer groups and Batang Kandis Jaya farmer groups fishing in Sungai Bangek Village Kelurahan Balai Gadang, Koto Tangah District, Padang, before being implemented IbM service activities is still very low. However, the motivation or desire of the community farmer groups IbM partners to undertake fish farming is huge. This can be seen from the wishes of the farmer groups IbM partners to master the technology of waste utilization water spinach, Ipomoea aquatica Forks, as a raw material alternative to artificial feed are relatively high. Further results of this public service activities to increase knowledge and skills of the community in the development of cultured technology and alternative fish feed so that farming activities can run well in both areas IbM partners.